Information seeking behavior of lawyers from Public Attorney's Office (PAO) and the Prosecutor's Office of Pasig City - Jaafar, Tadz Majal Ayesha V. (2007)
This study focused on the information seeking behavior of lawyers from the prosecutor's office and Public Attorney's Office of Pasig City. It aimed to find out the information searching strategies of lawyers; the types of materials lawyers use in searching; the format of materials they prefer; the feelings, behaviors and thoughts of lawyers during the search process, and, the issues and concerns of lawyers in the information seeking process.